Implementasi Algoritme Advance Encryption Standard (AES) pada Enkripsi dan Dekripsi QR-Code - Dwi Qunita Putri Ambeq Paramarta; Ari Kusyanti; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Data security are very important in today's technological development. Therefore, it is necessary to find a way to protect the confidentiality and the security from unauthorized accesses. One of the mechanism to increase data security is to use cryptography. There are many form of cryptography, one of them is Advance Encryption Standard Algorithm. This thesis uses AES Algorithm with the size of 128 bit expansion key. That will operate in a 4x4 array. In the state encryption process will go through several stages of Addroaundkey, Subbyte, Shiftrows, and Mixcolumns 10 times round. But in the last round Mixcolumns no longer process directly into the Addraoundkey process, and for the decryption process is a reverse process of the encryption process that InvAddrows, InvShiftrows, InvSubbyte, and InvMixcolumns use the same round key with the encryption process. AES is implemented in PHP programming language and applied to QR-Code because it is a labeling technology that can store data in the form of patterns that can be filled with information. From the results of the implementation of AES Algorithm can be concluded that this application can encrypt all types of characters in the form of strings, alphabet, numbers, and symbols. When decrypting QR-Code the application will activate the camera function and perform QR-Code scanning that will be plaintext again. The execution time of AES encryption and decryption is 0.0034 seconds for the encryption process and for the decryption process takes 0.0029 seconds.